DEVELOPMENT OF GENERAL COMPETENCE IN FUTURE HISTORY TEACHERS BASED ON THE KNOWLEDGE OF HISTORICAL IDEALS - Boltayeva Mohichexra (Journals Park Publishing, 2022)
This article discusses the formation and development of universal competence among future history teachers based on the knowledge of historical ideals, the introduction of new teaching methods into the teaching process, the departure from homogeneity, border patterns, the reformation of established stereotypes, the further increase of students' interest in science, and the formation of historical imagination and historical thinking in them.
Keywords: Method, sterotype, competence, thinking, unusual thinking, innovation, integration